Biological Control of Lesser Date Moth (Batrachedra. Amydraula/ mayrick) using the local parasitoid Goniozus omanensis - Al-Naabi, Samia Juma Suliman; Al-Zadgali, Najma Mahmood Somar; Al-Shidi, Rashid Saif (Journal of agricultural, environmental and veterinary sciences, 2023)
GONIOZUS OMANENSIS (Hym. Bethylidae) has been found to be the most common parasitoid of the lesser date moth, Batrachedra amydraula not only in Sultanate of Oman but also in neighboring Gulf states and other date palm growing parts of the world. It is one of the most important pests on date palm that is reported to cause more than 50% loss of the crop. Batrachedra amydraula, the lesser date moth is a species of moth of the Batrachedridae family reported from Bangladesh to western Saudi Arabia, Yemen, Israel, Iraq, and Iran, as well as most of North Africa. The larvae feed on Phoenix dactylifera. There are three generations per year in Sultanate of Oman. The first larvae appear in April and damage newly formed fruits. They are dormant from August to March of the following year, resting between the bases of the terminal fronds. Pupation takes place in March and adults emerge in April. Goniozus omanensis is primary parasitoid of lesser date moth Batrachedra amydraula. The present investigation involved successful rearing of parasitoid in the laboratory on larvae of Galleria mellonella and release in three date palm orchards as a bio-control agent against such a pest (one release, two releases, and three releases). The results showed that one release was sufficient to control 80% of the pest population in comparison with two (50%) and three releases (40%). About 0.1 % of pest was found from the bottom in comparison with emerging adults’ pests from infested fruits from the top of the palm.